Staff aging and turnover in african agricultural research: a case study on the agricultural research council and faculties of natural and agricultural sciences and veterinary sciences of the University of Pretoria - Liebenberg, Frikkie (International Food Policy Research Institute, 2011)
As part of a series of case studies (including Burkina Faso, Kenya, Senegal, South Africa, and Zambia) that assessed the status of and trends in human resource capacity, this study focused on staffing at the South African Agricultural Research Council (ARC) and the Faculty of Natural and Agricultural Sciences (FNAS&FVS) and Faculty of Veterinary Sciences (FVS) of the University of Pretoria (UP) during 2001-10. The specific characteristics studies were (1) the capacity of both research and support staff by gender, qualification level, and discipline; (2) the age profile of scientists; and (3) trends in staff recruitment and staff turnover. The results show that both the ARC and FNAS&FVS&FVS experienced an increase in the age of staff, although much more so at ARC than at FNAS&FVS. Unlike ARC, where research staff numbers have declined significantly over the past decade, FNAS&FVS recorded growth in researcher/lecturer capacity, although there has been a growing reliance on part-time appointments. Female participation in research has grown significantly at both the ARC and FNAS&FVS, albeit it in the junior (BSc-qualified) staff category at FNAS&FVS. In both cases it appears that the ability to compete with the private sector—and even the public sector in terms remuneration levels and the ability to attract and retain young researchers—is thus a constraint. Given the greater flexibility at universities in allowing staff to augment their income through consultancies, universities seems to be gaining ground over ARC, but this may not be sustainable in the long run.